Genome-wide Analysis and Expression Divergence of the Trihelix family in Brassica Rapa: Insight into the Evolutionary Patterns in Plants - Wenli Wang (Nature Portfolio, 2017)
Abstract Trihelix gene family is an important transcription factor (TF) family involved in plants’ growth and development. This extensive study of trihelix genes from Arabidopsis thaliana to Brassica rapa could shed light on the evolution in plants and support crop breeding. In this study, a total of 52 trihelix genes were identified in B.rapa. Whole-genome annotation, molecular-evolution and gene-expression analyses of all known trihelix genes were conducted. By statistics of the number of trihelix genes in each species, we found the expansion of trihelix gene family started with angiosperm evolution. And SIP1 was more preferentially retained than other subgroups (GT-1, GT-2, GTγ, SH4), consistent with the gene dosage hypothesis. Then we investigated the evolutionary patterns, footprints and conservation of trihelix genes in selected plants. The putative trihelix proteins were highly conserved, but their expression patterns varied. Half of these genes were highly expressed in all the selected organs but some showed tissue-specific expression patterns. Furthermore, among six abiotic stresses (Cold, Heat, PEG, NaCl, ABA and GA), most trihelix genes were activated by salt and ABA treatment. In summary, the phylogenetic, evolution and expression analyses of trihelix gene family in B.rapa establish a solid foundation for future comprehensive functional analysis of BraTHs.